2012
DOI: 10.1002/ijc.27899
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among offspring of women diagnosed with cancer: A population‐based cohort study

Abstract: One in five cancers in women is diagnosed prior to and during a woman's fertile years. Our study evaluates mortality risks in offspring of mothers with history of cancer. From the Swedish Multi-generation Register and the Cancer Register, we identified all 174,893 children whose mother had been diagnosed with cancer between 1958 and 2001. We categorized offspring into those born before (>1 year before), around (within 1 year before and after diagnosis) and after (>1 year after) their mother's cancer diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…This population-based cohort study shows that a parental cancer diagnosis was associated with an increased rate of death among children aged [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; this association appears to be slightly stronger among adolescents. Careful interpretation of the findings is needed because of the low absolute risk of death among these children and lack of information of other potential confounders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This population-based cohort study shows that a parental cancer diagnosis was associated with an increased rate of death among children aged [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; this association appears to be slightly stronger among adolescents. Careful interpretation of the findings is needed because of the low absolute risk of death among these children and lack of information of other potential confounders.…”
Section: Resultsmentioning
confidence: 99%
“…Verkooijen et al previously reported in a Swedish populationbased cohort study that offspring born over one year before their mother's cancer diagnosis had no significant increase in risk of allcause death up to over 25 years of age [15]. In the present study, we concentrated on children (1-18 years of age) having either a father or a mother with cancer, aiming to first, eliminate the potentially complicating effects of lifestyle and environmental factors on mortality beyond childhood and second, to contrast the impact of paternal and maternal cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This remained constant and was not affected by the timing of birth in relation to the cancer diagnosis. This is starkly different from mothers with cancer, where the timing of birth plays a major role, with offspring born around the time of diagnosis having a 66 % increased risk of death [ 32 ]. This is thought to be related to the intrauterine exposure to cancer treatment (chemotherapeutic agents and radiotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal cancer diagnosed during pregnancy has been associated with a higher risk of adverse birth outcome such as being born preterm and small for gestational age, and death due to perinatal and congenital conditions (46,47). One recent multicenter study indicated that prenatal exposure to maternal cancer did not lead to cognitive, cardiac, or general health problems among children at the age of 3 years (48).…”
Section: Prenatal Exposure To Parental Cancermentioning
confidence: 99%